Pengetahuan Ibu Hamil tentang Manfaat Sayur Bayam dalam Mencegah Anemia - Patriani, Sirly; Sinulingga, Selpyani; Jayanti, Ova (Jurnal Akademika Baiturrahim Jambi, 2024)
Anemia is the biggest public health problem in the world, especially for pregnant women. The prevalence of anemia in pregnant women worldwide is 41.8%. The prevalence of anemia in pregnant women is estimated in Asia at 48.2%. 60% of cases of anemia in pregnant women are due to iron deficiency. The risk of pregnant women who experience anemia faces the risk of death in pregnancy. Every year there are 500 thousand postpartum maternal deaths around the world as much as 20-40% of the main cause of death is anemia. The purpose of this study was to describe the knowledge of pregnant women about spinach in preventing anemia at BPM Muzilatulnisma, Jambi City. This research is a type of quantitative research with a descriptive analytic approach with a cross sectional design. Data collection in this study was carried out by distributing questionnaires, the research subjects in this study were 30 pregnant women selected by accidental sampling. This study was analyzed using univariate analysis. This research was conducted from September 2022 to July 2023. The results showed that 70% of pregnant women had good knowledge, and 30% had bad knowledge.